A comparison of function‐ and nonfunction‐based extinction treatments for inappropriate mealtime behavior. Issue 3 (19th March 2021) - Kirkwood, Caitlin A.; Piazza, Cathleen C.; Peterson, Kathryn M.
Abstract : Previous literature supports the use of functional analyses to prescribe treatments for children with feeding disorders (Bachmeyer et al., 2009). Nevertheless, clinicians often train caregivers to use healthy contingencies, independent of whether those contingencies are function based. However, it is unclear whether including nonfunction‐based contingencies differentially affects inappropriate mealtime behavior. In the current investigation, the caregivers of 3 children with feeding disorders provided escape from bites and drinks and attention following inappropriate mealtime behavior. Results of a functional analysis showed escape from bites or drinks, but not attention, reinforced inappropriate mealtime behavior. We then tested the effects of escape extinction when the feeder either provided or withheld attention following inappropriate mealtime behavior. Inappropriate mealtime behavior decreased and acceptance increased when the feeder implemented escape extinction independent of whether they provided or withheld attention. We discuss the implications of including nonfunction‐based components in the treatment of pediatric feeding disorders.